2015
DOI: 10.2174/1574886309666141022101956
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Dependence: A Case Report

Abstract: Physician should be aware about the addictive potential of pregabalin even in patients without a previous history of substance abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…History of substance misuse is typically associated with overuse of pregabalin [23][24][25][26]. Although tolerance to pregabalin has not been proven [27,28], its withdrawal syndrome may include agitation/ anxiety, craving, sweating, insomnia, fatigue, palpitations, tremors, and diarrhea [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…History of substance misuse is typically associated with overuse of pregabalin [23][24][25][26]. Although tolerance to pregabalin has not been proven [27,28], its withdrawal syndrome may include agitation/ anxiety, craving, sweating, insomnia, fatigue, palpitations, tremors, and diarrhea [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, pregabalin is approved for the treatment of epilepsy, neuropathic pain and generalized anxiety disorder (GAD). In the US pregabalin is approved for fibromyalgia, postherpetic neuralgia and neuropathic pain following spinal cord injury or diabetes, but not for GAD [1]. Additionally, case reports and smaller studies have suggested an effect for hypnotic-dependent insomnia [2], withdrawal of benzodiazepines [3] and alcohol dependence [4].…”
mentioning
confidence: 99%
“…The use of pregabalin has increased throughout the world and growing concerns about the abuse potential pregabalin have emerged [5][6][7]. Euphoria occurs as a frequent side effect of pregabalin [8] and several cases of overdose from recreational use have been reported [5,9,10]. Reports of tampering in which pregabalin was used by alternative routes of administration, i. e., nasal insufflation or venous injection, have also been reported [11,12].…”
mentioning
confidence: 99%
“…31 Literatürde, madde kötüye kullanım öyküsü olmadan pregabalin kullanım bozukluğu olan 3 hasta bildirimi yapılmıştır. [32][33][34] Bu hastalardan 1'inde; pregabalinin olağan dozlarda kullanıldığı (<300 mg/gün), sigara ile birlikte kullanımda öfori ve anksiyolitik etki üzerinde sinerjik etkileşim gösterdiği için tütün kullanım bozukluğu da geliştiği bildirilmiştir. 34 Bu özellikleri nedeni ile pregabalin 2010 yılında Avrupa Birliği'nde rekreasyonel psikoaktif maddeler listesine dâhil edilmiştir.…”
Section: Gabapenti̇noi̇dleri̇n Kötüye Kullanimiunclassified